Kinematic analysis of deployable parallel mechanisms. (January 2020) - Yang, Shuofei; Li, Yangmin
Inspired by the existing closed-loop deployable mechanisms and parallel mechanisms, a new kind of mechanisms, named deployable parallel mechanisms, is introduced in this paper, and the kinematic analysis is presented. As the combination of deployable mechanisms and parallel mechanisms, deployable parallel mechanisms have advantages of both the two kinds of mechanisms. They can be easily constructed by origami and folded from spatial structures into paper slices. Due to the parallel structures, they can be designed to have higher stiffness and larger volume compressibility than the existing deployable mechanisms. Thus, deployable parallel mechanisms have tremendous potential to be applied in the design of spatial solar panels, elastic reconfigurable robotic modules, etc. With reference to the kinematic analysis of parallel mechanisms, a finite and instantaneous screw method for kinematics of deployable parallel mechanisms is proposed, which is a generic method that is suitable for displacement and velocity modeling and analysis of any deployable parallel mechanism. A typical mechanism with symmetrical structure is taken as an example to show the validity of the proposed method, and simulation and experiment are carried out to verify the obtained results of kinematics. This paper puts forth the basic concepts of deployable parallel mechanisms and lays a theoretical foundation for their kinematic modeling and analysis.